A STUDY OF THE EFFECTS OF ROOM AIR TEMPERATURE ON CONCENTRATION PERFORMANCE OF HEALTHY AND ASTHMATIC OFFICE WORKERS IN THE TROPICS THROUGH PHYSIOLOGICAL, PSYCHOLOGICAL & PERCEPTUAL RESPONSES - MOEY SHEAU CHYI, ANGELINE (2011)
Bachelor's